Penerapan Model Discovery Learning Terhadap Keaktifan dan Hasil Belajar Siswa Kelas X MIPA SMAN 1 Piyungan Yogyakarta - Kawuri, Maria Yosephien Retna Tinon; Fayanto, Suritno (Jurnal Penelitian Pendidikan Fisika, 2020)
Activity learning is student activities during learning. Active learning is learning that supply and provides an opportunity for students to learn on their own or their activities that have an impact on learning outcomes. The purpose of this study was to describe the activity and student learning outcomes by applying the model of discovery learning. The research sample is Class X MIPA Public High School 1 Piyungan. This type of research is classroom action research consisted of two cycles of cycle 1 and cycle 2. Data collection techniques are using observation sheets and test sheets, As for the data analysis using descriptive analysis. The results of the analysis that studied physics Increased activity class X MIPA Public High School 1 Piyungan with discovery learningon the measurement of physical quantities in the academic year 2019/2020 of the first cycle in the first meeting and the second meeting was increased from 88.5% to 93.0%, i.e. 4.50%. In the second cycle increased from 92.1% to 97.0% there was an increase of 4.90. Improved physics learning outcomes of students of class X MIPA Public High School 1 Piyungan with discovery learning(DL) on the material for measuring physical quantities in the academic year 2019/2020 in cycle I to cycle II from 61% to 77.8% experiencing an increase of 16.8%. Improved learning outcomes show that the application of discovery learningcan be fun and make students interested and interested in learning.